PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID PADA MATERI RELASI DAN FUNGSI KELAS VIII SMP MENGGUNAKAN KODULAR - Ramadhani, Nur Insan; Berahman, Berahman; Ikmawati, Ikmawati; Haryaka, Usfandi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The field of learning is greatly influenced by technological advances, and mathematical skills are no exception. This research aims to share alternatives in delivering relation and function material for grade VIII junior high school students through an assessment of the validity and practicality of interactive learning media based on Kodular. The development of this product explores the stages of the 4D model (Definition, Design, Development, Dissemination). At the Definition stage, the initial analysis showed minimal enthusiasm and involvement of students and teacher-centered learning, so it was deemed necessary to innovate, namely an interactive learning application resulting from development using Kodular. The Design stage, designing a prototype by compiling test standards based on the formulation of learning objectives, choosing the Kodular website as the main platform with APK format, creating a learning application product called Math Voyager. At the Develop stage, students calculate and evaluate the Math Voyager learning media, which is validated by media and material experts. Analysis of the trial results using the Aiken V index. The validation value from the material expert is 0.72, the validation value from the media expert is 0.92, and the practicality value is 0.66. All of these index values are greater than 0.4 so it can be concluded that Math Voyager is valid and practical. The Disseminate stage, distributes Math Voyager to users via the Google Drive platform. This dissemination effort is carried out so that the Math Voyager media can be accessed by teachers and students.